(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The articlepresents theresults ofgrowing cottonundertheconditions ofsalinemeadow–alluvial soils in the Bukhara region, where the groundwater level is 2.0 - 2.5 m, using mineralized water for drip irrigation. When the pre-irrigation soil moisture was maintained at 70 – 80 - 65% of the field capacity, cotton was irrigated 15 times according to the 3 - 10 - 2 scheme. The crop was not irrigated during the period from germination to flowering, while during the flowering and boll formation stages, irrigation norms ranged from 273 to 437 m³/ha, with a total seasonal irrigation rate of 4483 m³/ha.As a result, compared to the control variant, water savings of 1594 m³/ha were achieved.